ANALISIS PENGARUH KUALITAS SUMBER DAYA MANUSIA TERHADAP PERTUMBUHAN EKONOMI SUMATERA BARAT - Dewi Zaini Putri; Melti Roza Adry (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2013)
The purposes of this research are to analyze the effect of (1) education index to economic growth, and (2) health index to economic growth. Types of research are descriptive and associative that show how exogen variable (X) effect endogenous variable (Y). Type of data is polled time series that combination of data or combinatioan from 19 regency/district in west Sumatera during 4 years and amount of data is 76 (n>30). Data analysis technique is linear regression analysis. Based on research that (1) education index has significant effect and poistive to economic growth, and (2) health index has significant effect and negative to economic growth. Based on reseach and analysis, government should increase facilities and infrastructure for education and health services to improve human qualities and increase the economic growth.